Interregional trade and money flows in Nigeria, 1964 - Hay, Alan M.; Smith, Robert Henry Tufrey (Ibadan, Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1970)
This book provides an estimates in volume of Nigeria international trade in 1964. the study include a benchmark which may be useful in planning at a critical period of Nigeria's development..
Includes index
Includes bibliographical references.
II 18/01/2019
Loans
Keywords: Smith H.T R; Nigeria